A geógrafa Isabel André, notas de testemunho de um percurso inovador, brilhante e livre - Rêgo, Patrícia Maria Alves Pedro Fonseca (2017)
A geógrafa Isabel André, notas de testemunho de um percurso inovador, brilhante e livre